2011
DOI: 10.1177/0022034511402083
|View full text |Cite
|
Sign up to set email alerts
|

Global Oral Health Inequalities

Abstract: The birth prevalence of orofacial clefts, one of the most common congenital anomalies, is approximately one in 700 live births, but varies with geography, ethnicity, and socio-economic status. There is a variation in infant mortality and access to care both between and within countries, so some clefts remain unrepaired into adulthood. Quality of care also varies, and even among repaired clefts there is residual deformity and morbidity that significantly affects some children. The two major issues in attempts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 99 publications
0
39
0
3
Order By: Relevance
“…Previous studies showed a worldwide prevalence of 0.1% for CL/P [15]. While Asian populations generally have the highest rates, rates vary widely, reflecting genetic, environmental and health equality factors [1]. A study in Jordan of 25,440 infants reported incidence of facial cleft deformities to be 0.2% [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed a worldwide prevalence of 0.1% for CL/P [15]. While Asian populations generally have the highest rates, rates vary widely, reflecting genetic, environmental and health equality factors [1]. A study in Jordan of 25,440 infants reported incidence of facial cleft deformities to be 0.2% [15].…”
Section: Discussionmentioning
confidence: 99%
“…While the worldwide prevalence of such deformities is about 1.5 per 1,000 live births, the rate varies six-fold for CL/P and three-fold for CP [1]. Reports in Asian populations put overall rates around 1.76 to 1.81, reflecting the higher prevalence in this region [2], [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As knowledge of genetics and of gene-environment interaction in the aetiology of OC improves, clinical genetics is becoming increasingly important specialty to ensure accurate diagnosis and allow appropriate genetic counselling [3]. Therefore, clinical genetic approach improves accuracy, consistency, and reliability of clinical descriptions and aetiological assessment which are critical to genotype-phenotype correlations.…”
Section: Discussionmentioning
confidence: 99%
“…Cleft of the lip and/or palate (CL/P) is one of the most common facial malformations 1– 3 and a societal burden, affecting the patient ability to eat and speak and influencing social integration 4 . Non-syndromic CL/P, accounting for about 70% of CL/P, is considered closely related to genetic and environmental factors 5 .…”
Section: Introductionmentioning
confidence: 99%